Spatholobus suberectus Dunn Water Extract Ameliorates Atopic Dermatitis–Like Symptoms by Suppressing Proinflammatory Chemokine Production In Vivo and In Vitro - Song, Hyun-Kyung; Park, Sun Haeng; Kim, Hye Jin; Jang, Seol; Kim, Taesoo (Frontiers in Pharmacology, 2022)
Spatholobus suberectus Dunn, a traditional Chinese herbal medicine, has various pharmacological activities such as anti-inflammatory properties. However, to the best of our knowledge, its therapeutic effect on atopic dermatitis (AD) has not been investigated. In this study, we explored the effect of S. suberectus Dunn water extract (SSWex) on AD in vivo and in vitro. In Dermatophagoides farina extract (DfE)-treated NC/Nga mice, oral administration of SSWex alleviated AD-like symptoms, such as ear thickness, dermatitis score, epidermal thickness, immune cell infiltration, and levels of AD-related serum parameters (Immunoglobulin E, histamine, and proinflammatory chemokines). In HaCaT cells, production of proinflammatory chemokines induced by interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α) was inhibited by SSWex pretreatment. SSWex treatment inhibited the phosphorylation of mitogen-activated protein kinase and activation and translocation of transcriptional factors, such as signal transducer and activator of transcription 1 and nuclear factor kappa B in IFN-γ/TNF-α-stimulated HaCaT cells. These results indicate that SSWex may be developed as an efficient therapeutic agent for AD.